Zawartość Regestru krotkiego na rozmaite niemocy a choroby Ludzkie… w polskiej wersji poradnika Piotra Krescencjusza - Kamper-Warejko, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The article describes the medical vocabulary contained in the register of diseases included at the beginning of the Polish translation of Petrus de Crescentius’s handbook (1571; this material is also representative of an older version of the text from 1549). After an analysis of the origins of the register, the general semantic structure of the names that it contained was characterized and set in the context of 16th-century Polish, also against the background of Falimirz’s herbarium and other texts. An attempt was made to establish the reference of the names and classify them using the division proposed by Lucyna Jankowiak (2005) and Słownik Polszczyzny XVI wieku (Dictionary of 16th-century Polish). The analysis showed that most of the names are known to the Polish language of the time; there are, however, some new ones not recorded in the said dictionary. The core of the vocabulary extracted from the register are the names of diseases (among them, the names of diseases affecting the digestive system appeared most frequently, followed by the names of diseases of the skin, nervous and sensory organs, genitourinary and respiratory systems), but three other groups of names were also isolated.